2017
DOI: 10.1038/ncomms15892
|View full text |Cite
|
Sign up to set email alerts
|

Single-virus genomics reveals hidden cosmopolitan and abundant viruses

Abstract: Microbes drive ecosystems under constraints imposed by viruses. However, a lack of virus genome information hinders our ability to answer fundamental, biological questions concerning microbial communities. Here we apply single-virus genomics (SVGs) to assess whether portions of marine viral communities are missed by current techniques. The majority of the here-identified 44 viral single-amplified genomes (vSAGs) are more abundant in global ocean virome data sets than published metagenome-assembled viral genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
314
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(321 citation statements)
references
References 65 publications
7
314
0
Order By: Relevance
“…Indeed, although this contig from Zn5 recruited reads from Zn24, it could not be assembled in Zn24 likely due to its high microdiversity. As aforementioned, this is a problem also encountered by others when assembling metaviromes (Martinez‐Hernandez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, although this contig from Zn5 recruited reads from Zn24, it could not be assembled in Zn24 likely due to its high microdiversity. As aforementioned, this is a problem also encountered by others when assembling metaviromes (Martinez‐Hernandez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In light of this hypothesis, the high abundance and diversity of actinoviruses may result from an arms race with their hosts, leading to genomic diversification of the hosts to avoid mortality induced by a high viral load. It should be noted that such microdiversification of viral genomes poses challenges for metagenomic assembly (Martinez‐Hernandez et al ., ; Roux et al ., ; Warwick‐Dugdale et al ., ); indeed, 109 LBVCs encoded the actinoviral hallmark whiB gene (Supporting Information Dataset S1), suggesting that the majority of actinoviral genomes were not recovered as LBVGs (i.e., circularly assembled). Although further investigation is beyond the scope of the present study, our results revealed that, analogous to their hosts, actinoviruses are one of the most diverse, abundant, ubiquitous, and active viral groups in freshwater systems.…”
Section: Resultsmentioning
confidence: 99%
“…The North Pacific Subtropical Gyre is a representative habitat of oligotrophic oceans that cover ≈40% of the Earth´s surface. For instance, the chlorophyll a content in the analysed North Pacific Subtropical Gyre transcriptomic samples (0.21 ± 0.044 SD μg/L; available at http://scope.soest.hawaii.edu/data/hoelegacy/) (Aylward et al ., ) were very similar to that of the western oligotrophic Mediterranean Sea, from where 37‐F6 virus was obtained (Martinez‐Hernandez et al ., ).…”
mentioning
confidence: 97%
“…B) at an average amino acid identities (AAI) between 50% and 81% with very high gene synteny (Fig. S2), and in all cases, at <95% average genome nucleotide identities (gANI), approximating genus‐level relatedness or even probably in some cases to subfamily level (Mizuno et al ., ; Roux et al ., , ; Martinez‐Hernandez et al ., ). In addition, most of these viral contigs from Osaka Bay related to vSAG 37‐F6 had the specific capsid marker gene, representing viral group 37‐F6 (gene 9), which was the most abundant marine viral protein (Brum et al ., ; Martinez‐Hernandez et al ., ).…”
mentioning
confidence: 97%
See 1 more Smart Citation